2022
DOI: 10.1021/jacs.1c12072
|View full text |Cite
|
Sign up to set email alerts
|

Superatom Regiochemistry Dictates the Assembly and Surface Reactivity of a Two-Dimensional Material

Abstract: The area of two-dimensional (2D) materials research would benefit greatly from the development of synthetically tunable van der Waals (vdW) materials. While the bottom-up synthesis of 2D frameworks from nanoscale building blocks holds great promise in this quest, there are many remaining hurdles, including the design of building blocks that reliably produce 2D lattices and the growth of macroscopic crystals that can be exfoliated to produce 2D materials. Here we report the regioselective synthesis of the clust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Transition-metal chalcogenide clusters are an attractive class of building blocks for assembling solid-state materials. One of the most common such clusters is the octahedral metal chalcogenide TM 6 E 8 L 6 (see structures in Figure ), where TM is transition metal, E is chalcogen, and L is ligand. Prepared in solutions or in the solid state, these clusters can be highly stable, have charge donor/acceptor characteristics, and can form multicomponent solids with complementary units while maintaining their internal structures. Functional solids made using these building blocks offer programmable properties, including tunable and switchable magnetic ordering, electrical conductivity, optical properties, and thermal transport. , One of the key advantages over traditional atomic solids is that the electronic and magnetic characteristics of the individual building blocks can be programmed preassembly, offering unique levels of control over the properties of the assembled materials. Octahedral Fe 6 clusters synthesized in the Betley group on a templating ligand scaffold have even been shown to achieve giant spin ground states up to S = 19/2 with electronic structure characteristic of superatoms. …”
Section: Introductionmentioning
confidence: 99%
“…Transition-metal chalcogenide clusters are an attractive class of building blocks for assembling solid-state materials. One of the most common such clusters is the octahedral metal chalcogenide TM 6 E 8 L 6 (see structures in Figure ), where TM is transition metal, E is chalcogen, and L is ligand. Prepared in solutions or in the solid state, these clusters can be highly stable, have charge donor/acceptor characteristics, and can form multicomponent solids with complementary units while maintaining their internal structures. Functional solids made using these building blocks offer programmable properties, including tunable and switchable magnetic ordering, electrical conductivity, optical properties, and thermal transport. , One of the key advantages over traditional atomic solids is that the electronic and magnetic characteristics of the individual building blocks can be programmed preassembly, offering unique levels of control over the properties of the assembled materials. Octahedral Fe 6 clusters synthesized in the Betley group on a templating ligand scaffold have even been shown to achieve giant spin ground states up to S = 19/2 with electronic structure characteristic of superatoms. …”
Section: Introductionmentioning
confidence: 99%
“…The purpose of the present paper is to examine if the periodic patterns extend to vibrational and optical properties in octahedral ligated metal chalcogenide clusters ligated with CO ligands. Our interest in these metal chalcogenide clusters stems for their facile synthesis into cluster assembled materials. These metal chalcogenide superatoms are promising building blocks for new materials because of their highly stable cores and the variety of approaches that may be used to form the clusters into different frameworks. Highly ordered ionic cluster assembled materials may be formed via charge transfer. ,, Metal chalcogenide clusters may form new frameworks through the stable cores fusing into multiple cored clusters, chains, and sheets. , Also, ligands may link the clusters via molecular bridges into a different class of highly ordered materials. , Furthermore, through a judicial choice of ligands, one can control the electronic and redox properties of the clusters. Our investigations focus on theoretical studies of optical absorption, infrared spectra, binding energies, and various other cluster properties of octahedral transition metal chalcogenide clusters TM 6 Se 8 (CO) 6 (TM: W–Pt).…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25][26][27] Consequently, superatoms are ideal atomic-level bottom units that meet Feynman's expectations, and bottom-up assembly based on superatoms has become an important research direction. [9,[28][29][30] Among the superatoms, it was found that the light actinide (An) elements Ac, Th, Pa, U and Pu embedded in fullerene C 28 can form a series of stable endohedral metallofullerene (EMF) superatomic structures with gradual electron arrangement. [31][32][33][34][35] In particular, the two unpaired electrons on the C 28 cage facilitate bonding with neighboring units by spinpolarized magnetic coupling.…”
Section: Introductionmentioning
confidence: 99%